On competition - Porter, Michael E., 1947- (Boston, MA : Harvard Business School Pub., 2008)
Porter was the first to bridge the field of industrial organization with the field of management, effectively forging the new field of competitive strategy.
The five competitive forces that shape strategy / Michael E. Porter -- What is strategy? / Michael E. Porter -- How information gives you competitive advantage / Michael E. Porter and Victor E. Millar -- Strategy and the Internet / Michael E. Porter -- From competitive advantage to corporate strategy / Michael E. Porter -- The competitive advantage of nations / Michael E. Porter -- Clusters and competition : new agendas for companies, governments, and institutions / Michael E. Porter -- Competing across locations : enhancing competitive advantage through a global strategy / Michael E. Porter -- Green and competitive : ending the stalemate / Michael E. Porter and Claas Van Der Linde -- The competitive advantage of the inner city / Michael E. Porter -- Redefining competition in health care / Michael E. Porter and Elizabeth Olmsted Teisberg -- Philanthropy's new agenda : creating value / Michael E. Porter and Mark R. Kramer -- The competitive advantage of corporate philanthropy / Michael E. Porter and Mark R. Kramer -- Strategy and society : the link between competitive advantage and corporate social responsibility / Michael E. Porter and Mark R. Kramer -- Seven surprises for new CEOs / Michael E. Porter, Jay W. Lorsch, and Nitin Nohria.
"A Harvard business review book."
Includes bibliographical references and index.
Description based on print version record.
Keywords: Competition, International; Comparative advantage (International trade); Industrial policy; Environmental policy; Social policy; Concurrentie; Strategische planning; Concurrentiebeleid; Aufsatzsammlung; Internationaler Wettbewerb; Wettbewerbsstrategie; Comparative advantage (International trade); Competition, International; Environmental policy; Industrial policy; Social policy; Competencia internacional; Competencia económica; Ventaja comparativa (comercio internacional).; Industria y estado; Política ambiental; Política social; BUSINESS & ECONOMICS / Exports & Imports; BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / International / Marketing; POLITICAL SCIENCE / International Relations / Trade & Tariffs; elektronické knihy; electronic books